Obesity and cesarean section rate among low‐risk primiparous women in Victoria, Australia: A population‐based study - Alemayehu Mekonnen; Glyn Teale; Vidanka Vasilevski; Linda Sweet (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Women living with overweight, or obesity are at risk of pregnancy and birth complications. This study investigated the trend and associations between overweight and obesity on cesarean births and their contribution to cesarean births among low‐risk primiparous women in Australia. Material and Methods Body mass index data were obtained for 219, 950 primipara (aged 20─34 years) with singleton, term pregnancies without malpresentations from the Victorian Perinatal Data Collection registry (2010─2019). Women were grouped according to body mass index and logistic regression analyses were performed to assess the trend and associations of overweight and obesity with cesarean births. The contribution of overweight and obesity to cesarean births were estimated using population attributable fraction. Results The prevalence of cesarean birth was 29.7%, and the prevalence increased by 20%, from 27.6% in 2010 to 33.2% in 2019. Being overweight or obese was independently associated with an increased likelihood of cesarean births in the overall sample (adjusted OR (AOR) 1.46; 95% CI 1.42–1.50 and AOR 2.05, 95% CI 1.98–2.11, respectively). However, overweight was not an independent risk factor when the analysis was limited to elective cesarean births. Induction of labor was significantly higher among women who were overweight (AOR 1.38; 95% CI 1.35–2.42), or obese (AOR 2.18 95% CI 2.12–2.25). The combined overweight and obesity contributed to 14.8% of cesarean births but the increasing trend of cesarean births was not explained solely by changes in overweight or obesity rates. Conclusions Obesity and overweight, combined, are responsible for a significant proportion of cesarean births. However, overweight and obesity alone do not provide enough insight into the increasing trend of cesarean birth. While further investigation of potential contributors is needed, initiatives to reduce cesarean births in Australia may benefit better by including measures, such as health education to prevent overweight and obesity prior to conception.